TeleHealth system for elderly - health record application - Liu, Xuan. (2013)
Nowadays health problem has aroused people attention. The research shows that there is an increasing demand for the health monitoring device as people become more health cautious. For the elderly, the health monitoring and evaluate by a doctor will become the essential part in order to identify and address a medical problem early. But in the mean time, they also face some related health monitoring issues, such as time consuming for checking up in clinic, being unable to schedule regular appointments due to busy lifestyles and inconvenient to visit clinic and so on. Thus, a system needs to be developed for solving these problems.